Think smarter : critical thinking to improve problem-solving and decision-making skills - Kallet, Mike, 1953- (Hoboken, New Jersey : Wiley, 2014)
"Critical thinking is a process that lets your brain do more for you as you make decisions, solve problems, make plans, and execute them. Much of the current content on this subject is academic focused. Think Smarter, Not Harder focuses instead on applying critical thinking techniques to everyday business issues. This application results in higher quality problem solving and decision making, more innovation, faster decisions, opportunity recognition, mistake avoidance, and higher productivity. The skills learned in this book can be applied to: New product ideas and creation Short and long term business strategies Improved operational efficiency Crisis management Customer care improvement, and Revenue generation and cost reduction strategies "--
Machine generated contents note: Dedication Acknowledgements Foreword Section I: Introduction and the Framework for Critical Thinking Chapter 1: What is Critical Thinking? Benefits of Critical Thinking Chapter 2: When to Use Critical Thinking Chapter 3: The Framework and Tools Clarity Conclusions Decisions Section II: Clarity Chapter 4: Empty Your Bucket The Bucket Getting Started with Emptying Your Bucket Chapter 5: Inspection Inspection Getting Started with Inspection Chapter 6: Why? Why Why? Ask why to get to I don't know Getting Started with Why Chapter 7: So What? So What? So What: Your Company or Product YOUR So What? Getting Started with So What Chapter 8: Need What is the Necessity? Great Teams and Need Need and Survival Getting Started with Need Chapter 9: Anticipatory Thinking What's Next? Getting Started with Anticipatory Thinking Chapter 10: What Else? What Else Could This Be? Getting Started with What Else Chapter 11: The Ingredient Diagram Ingredients of Your Headscratcher Getting started with the Ingredient Diagram Chapter 12: Vision What is Your Vision? Getting Started with Vision Chapter 13: The Thinking Coach The Role of a Thinking Coach Why Be a Thinking Coach? Examples of a Thinking Coach If You Have the Experience, Why Not Communicate That? Ten Rules of a Thinking Coach Getting Started with Being a Thinking Coach Section III: Conclusions Chapter 14: Summary of Clarity Clarity - Getting Clear about Your Headscratcher Getting Started Practice Clarity - Not About Solving the Problem, but Generates Solutions When Am I Done with Clarity? Can I Use Critical Thinking by Myself and Not with a Group? Chapter 15: It's all about The Premise Deduction Induction It's All About the Premise Chapter 16: Facts Facts are Absolute Truth Use so what with facts Fact or Not Fact Chapter 17: Observations Observations are Abundant Chapter 18: Experiences Your Experiences So What? Chapter 19: Beliefs Beliefs - Your Value System When Beliefs Are Different Chapter 20: Assumptions Assumptions are Key Chapter 22: Credibility How Credible is the Premise? Credibility of Facts and Observations Why Do People Lose Credibility? Getting Started with Credibility Chapter 23: Consistency The Consistency of Your Premise Components Getting Started with Consistency Chapter 24: Triangular Thinking Triangular Thinking: Estimating the Unknown Getting Started with Triangular Thinking Chapter 25: Change The Premise and Change Helping People Get Over Change Getting Started with Change Chapter 26: Influencing and Persuading Influence and Persuasion Using the Premise to Influence Using the Premise to Persuade Maybe you need to be persuaded? Getting Started with Influencing and Persuading Section: IV Conclusions and Innovation Chapter 27: Outside-the-Box Thinking Ask What If and What Other Getting Started with Thinking Outside-the-Box Chapter 28: Abductive Thinking Abductive Thinking Old Dog Thinking Knowledge with No Experience Old Dog Thinking Cures Getting Started with Abductive Thinking Chapter 29: Impossible Thinking Thinking How to Accomplish the Impossible Getting Started with Impossible Thinking Exercises for Impossible Thinking Chapter 30: Summary of Conclusions Conclusions - Creating Solutions Getting Started Conclusions - Sorry, You're Not Quite Done! Section V: Decisions Chapter 31: Who, Need and When Whose Decision Is This, Anyway? Need, Again! When Does This Decision Need to Be Made? Getting Started with Who, Need and When Chapter 32: Criteria Without Criteria, Nothing Is Decided Getting Started with Criteria Chapter 33: Risk Eleven Risk Factors Using the Eleven Factor Model What Is Too Risky? Getting Started with Risk Chapter 34: Summary of Decisions Decisions - Taking Action Getting Started Are we done yet? Chapter 35: Critical Thinking: Summary and Suggestions Critical Thinking Summary Critical Thinking - Let's Begin .
Includes index.
Keywords: Problem solving; Decision making; Critical thinking; BUSINESS & ECONOMICS / Decision-Making & Problem Solving